INTEREST OF BATAKNESE AND JAVANESE YOUTH IN AGRICULTURE IN BINJAI DISTRICT, LANGKAT REGENCY, NORTH SUMATRA PROVINCE - Annisah; Dwi Febrimeli; Mahmudah; Rudi Hartono (Politeknik Pembangunan Pertanian Bogor, 2023)
The low interest of young people in the agricultural sector is increasing from year to year. It is because businesses in the agricultural industry are less profitable and not promising jobs. This research aims to determine the factors that affect the interests of tribe youth Batak and Java in agriculture and the difference of interest between youth tribe Batak dan Java. This research was conducted in the Binjai District of Langkat Regency. The data collection method is used by interviews and questionnaires tested for validity and reliability—the data analysis method uses multiple linear regression and tests. The result of the research indicates that there is a difference between the interest of young Batak and Javanese tribes in the field of agriculture. Partially, prestige and family environment have an inverse effect on the interest of your Batak in agriculture and factor social statute (3,246) positively influences the interest of the youth tribe of your java. The elements of prestige, family environment, education, experience, social environment, social statute, culture and technology contributed 52,7% to the interest of youth Batak. And 75,8% of factors prestige, family environment, education, experience, social environment, social statute, culture and technology influence the interest of Javanese.